When Institutional Multiplicity Backfires: The Battle Over the Jurisdiction to Prosecute Politicians for Administrative Improbity in Brazil - Vivian Pereira Ferreira (Revista Direito GV)
Abstract Brazilian Administrative Improbity Act (Law n. 8.429/1992) created a different form of punishment for corrupt behavior and it may be understood as an attempt to introduce institutional multiplicity in the country’s legal system. Even though the law has been largely applied and resulted in the imposition of sanctions, it also has limitations: cases often taken several years before being concluded and the recovery of assets has not been substantial overtime. This paper seeks to elucidate some of the reasons why this might have happened. We argue that poor legal design combined with legal implementation problems resulted in delays in final judicial decisions. This paper focuses on a topic that has occupied Brazilian courts for a long time: determining in which jurisdiction should authorities and politicians be tried for administrative improbity. We describe the most prominent Supreme Court’s decisions about the theme and try to draw institutional lessons from them, by developing feasible solutions to improve the enforcement of Law n. 8.429/1992.